Optimasi formula krim body scrub ekstrak lamun (Enhalus acoroides) terenkapsulasi - Made Pharmawati; Luh Putu Wrasiati (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Body scrub cream is used to clean and nourish the skin. Several illegal creams were reported to contain harmful chemicals. Some plant extracts can replace chemical compounds because they can lighten the skin. Enhalus acoroides is one of the seagrass species that is widely distributed in Indonesia. Leaf extract of E. acoroides was found to contain phenolic, tannin, and flavonoid. Due to the bioactive compounds in the E. acoroides extract can be added to cosmetic products such as body scrub cream. This study aimed to analyze the effect of the addition of encapsulated E. acoroides extract on the characteristics of the body scrub cream and determined the concentration of the encapsulated E. acoroides extract, which produced the best body scrub cream. The extraction was done using chloroform: ethanol (9:1) and encapsulation using maltodextrin and tween. The body scrub cream was made in two phases, the oil phase and the water phase. The concentrations of the encapsulated E. acoroides extract tested were 0%, 0.5%, 1%, 1.5%, 2%, 2.5%. The characteristics evaluated were homogeneity, pH, viscosity, spreadability, stickiness, IC50, and organoleptic test for color and scent. The results showed that the body scrubs were homogenous. The pH values were 5.43-6.66, and viscosity was 34400-46400cp which are in the range of SNI for cosmetic products. The spreadability values were 4.03-5.5cm, and stickiness was 4.8-6.91sec. The antioxidant capacity (IC50) ranged from 147.38 to 157.64 ppm, and the overall acceptance scores were 5 to 6.80. Based on the effectivity index and statistical analyses of physical-chemical characteristics, the best concentration of encapsulated E. acoroides extract was 2%. These findings indicate the potential of encapsulated E. acoroides extracts to improve skin health.